2018
DOI: 10.1017/hpl.2017.38
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed LD side-pumped MgO: LN electro-optic cavity-dumped 1123 nm Nd: YAG laser with short pulse width and high peak power

Abstract: We report a cavity-dumped 1123 nm laser with narrow pulse width and high peak power by an MgO: LN crystal electro-optic (EO) modulator. Based on the structural optimization design of a folded biconcave cavity using the 808 nm pulsed laser diode (LD) side-pumped ceramic Nd: YAG rod, output pulses with maximum pulse energy and peak power up to 39.6 mJ and 9.73 MW were obtained, corresponding to 100 Hz repetition rate and 4.07 ns pulse width. The instabilities of pulse width and pulse energy were $\pm$1.55% and $… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…6(b), red curve). The power instability ρ and the noise Γ L-RMS of the passively Q-switched pulsed laser at the maximum average power were measured to be ±5.23% and 5.21% within a 4 h period using the following equations: [30,31]…”
Section: Bp and Bc Are Not Placed In The Cavitymentioning
confidence: 99%
“…6(b), red curve). The power instability ρ and the noise Γ L-RMS of the passively Q-switched pulsed laser at the maximum average power were measured to be ±5.23% and 5.21% within a 4 h period using the following equations: [30,31]…”
Section: Bp and Bc Are Not Placed In The Cavitymentioning
confidence: 99%
“…The specific process parameters for the preparation of coating were shown in table 3. The Ni-based alloy coating prepared by supersonic particle deposition was remelted by the ZKSX1000 continuous type laser cladding system, because the pulse laser may cause deep damage to the material surface [30][31][32][33]. Argon was used as protective…”
Section: Supersonic Particle Deposition and Laser Remeltingmentioning
confidence: 99%
“…In comparison, the lower growth temperature and shorter growth period of its ceramic counterpart could greatly reduce both AD production in the lattice and manufacture costs. Moreover it is much easier to achieve uniform ion co‐doping in LuAG:Ce ceramic 12,13 . In addition, Chen Hu et al recently reported LuAG:Ce ceramic to have excellent radiation damage resistance, making it a very attractive material for HEP experiments 14 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover it is much easier to achieve uniform ion co-doping in LuAG:Ce ceramic. 12,13 In addition, Chen Hu et al recently reported LuAG:Ce ceramic to have excellent radiation damage resistance, making it a very attractive material for HEP experiments. 14 Regarding the negative effects of defects in LuAG, "defect engineering" is thought to be an effective solution.…”
mentioning
confidence: 99%